PERLINDUNGAN HUKUM ANAK DALAM KEJAHATAN PORNOGRAFI DAN UPAYA PEMERINTAH DALAM MENCEGAH KEJAHATAN PORNOGRAFI DI INDONESIA - IDA BAGUS WIRYA DHARMA (Universitas Mahasaraswati K. Mataram, 2022)
A number of files related to child pornography often appear on several sites and forums on the internet. This is a reflection of the impact of technological developments which were originally created to facilitate human life. The issue of child pornography began in the nineteenth century after the invention of the camera. At that time, the issue of child pornography only developed in hard copy form. The Internet era in the early 1980s dramatically changed the scale and nature of the child pornography problem and required a new approach to research and control.The study used in conducting this thesis research is normative legal research. Normative legal research is legal research that puts the law as a building system of norms. The system of norms in question is about principles, norms, rules of statutory arrangements, court decisions, agreements and doctrines.The results of the thesis research are related to the juridical basis of children's rights related to the crime of child pornography in cyberspace based on the ITE Law, namely Article 26; Article 27 paragraph (1); Article 36 and Article 37 and forms of legal protection for children's rights in pornography crimes in Indonesia are of two types: repressive forms of protection (Penal) and preventive forms of protection (Non-Penal)